Life cycle assessment of LPG and diesel vehicles in Korea - Kim, Min June; Lee, Eun Jun; Kim, Chul-Jin; Hong, Ung Gi; Park, Deuk Soo; Shin, Haebin; Lee, Kwan-Young (The Korean journal of chemical engineering, 2021)
With LPG automobile deregulation in 2019, the demand for LPG automobiles has increased in Korea; therefore, a comparison of the eco-friendliness of LPG and other petroleum-based vehicles has become necessary. We conducted a well-to-wheels (WTW) analysis of diesel and LPG fuel in Korea. GREET, PRELIM, and GHGenius models were utilized to calculate and appropriately allocate the energy use and greenhouse gas (GHG) emission in the life cycle process of diesel and LPG fuel. In the well-to-tank (WTT) step, the GHG emissions of LPG were lower than that of diesel because of the lower energy consumption of LPG in fuel production. For the WTW comparison, we selected four automobiles currently sold in Korea and a 1,500kg curb weight model. The WTW GHG emissions of the LPG automobiles were lower than those of the diesel SUV and the 1 ton truck. On the other hand, the WTW GHG emissions of diesel automobiles were lower in the sedans and in the 1,500 kg model. Finally, it was verified that LPG automobiles were advantageous in terms of GHG emission in the SUV and one-ton truck, although the GHG emissions of diesel and LPG vehicles can vary depending on the fuel economy of the vehicles.